Tracking Wage Inequality Trends with Prices and Different Trade Models : Evidence from Mexico - Halliday, Timothy; Lederman, Daniel; Robertson, Raymond (World Bank, Washington, DC, 2015)
Mexican wage inequality rose following Mexicos accession to the General Agreement on Tariffs and Trade/World Trade Organization in 1986. Since the mid-1990s, however, wage inequality has been falling. Since most trade models suggest that output prices can affect factor prices, this paper explores the relationship between output prices and wage inequality. The rise of inequality can be explained by the evolution of the relative price of skill-intensive goods relative to unskilled-intensive goods, but these prices flattened by 1999 and thus cannot explain the subsequent decline in wage inequality. An alternative trade model with firm heterogeneity driven by variations in the relative price of tradable relative to non-tradable goods can explain the decline in wage inequality. The paper compares this model’s predictions with Mexican inequality statistics using data on output prices, census data, and quarterly household survey data. In spite of the models simplicity, the model’s predictions match Mexican variables reasonably well during the years when wage inequality fell.